Anthropometric and Fitness Profile of Senior Basketball Players [Perfil Antropométrico y Condición Física de Jugadores Veteranos de Básquetbol] - Herrera-Valenzuela, T (Universidad de la Frontera, 2015)
The demographic and social changes are causing a gradual increase in people over 60 years worldwide, situation thar is similar in Chile, so the study of variables related to this group of the population becomes important. In this regard, the aim of this study is to determine the anthropometric and physical fitness profile of senior basketball players (SBP). This is a descriptive, cross-sectional, quantitative research. The sample included 30 SBP (age 66.7-6.8 years) belonging to the league of the Senior Basketball Association of the Araucanía Region, Chile. The dependent variables studied correspond to body composition, somatotype and fitness (strength, endurance, flexibility, agility and dynamic balance). Results indicate that the SBP showed endomorphic, mesomorphic and ectomorphic values of 4.1, 6.1 and 1.0, respectively, as meso-endomorphs with a muscle mass of 45% and body fat of 24.5%. Compared to age and sex counterparts, SBP exhibit equal (40% of SBP) or even higher (40% of SBP) values for physical fitness perfomance variables. In conclusion, SBP have a favorable anthropometric and physical fitness profile for their age and sex, suggesting that the systematic practice of basketball would have a positive impact on body composition and physical fitness-function in older adults, however more experimental research is needed to corroborate this. © 2015, Universidad de la Frontera. All rights reserved.